2001
DOI: 10.1095/biolreprod65.3.784
|View full text |Cite
|
Sign up to set email alerts
|

Capacitation Is Associated with Tyrosine Phosphorylation and Tyrosine Kinase-Like Activity of Pig Sperm Proteins1

Abstract: Capacitation represents the final maturational steps that render mammalian sperm competent to fertilize, either in vivo or in vitro. Capacitation is defined as a series of events that enables sperm to bind the oocyte and undergo the acrosome reaction in response to the zona pellucida. Although the molecular mechanisms involved are not fully understood, sperm protein phosphorylation is associated with capacitation. The hypothesis of this study is that protein tyrosine phosphorylation and kinase activity mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
135
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 60 publications
(69 reference statements)
17
135
1
2
Order By: Relevance
“…The situation of phosphorylated proteins at the principal piece of the flagellum has been related to motility hyperactivation and to the presence of A-kinase anchoring proteins (which anchor PKA) located in the fibrous sheath of the sperm flagellum in several species (Carrera et al 1996, Mandal et al 1999, Jha & Shivaji 2002a, Pommer et al 2003. Conversely, a capacitation-related redistribution of phosphotyrosine residues to the acrosome has been reported in humans (Naz et al 1991), boars (Tardif et al 2001, Dube et al 2005, bulls (Cormier & Bailey 2003) and buffalo (Roy & Atreja 2008). Moreover, other studies have revealed that certain tyrosine phosphoproteins become localized to the sperm surface overlying the acrosome during capacitation suggesting a key role of these proteins in sperm-zona binding (Asquith et al 2004, Piehler et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation of phosphorylated proteins at the principal piece of the flagellum has been related to motility hyperactivation and to the presence of A-kinase anchoring proteins (which anchor PKA) located in the fibrous sheath of the sperm flagellum in several species (Carrera et al 1996, Mandal et al 1999, Jha & Shivaji 2002a, Pommer et al 2003. Conversely, a capacitation-related redistribution of phosphotyrosine residues to the acrosome has been reported in humans (Naz et al 1991), boars (Tardif et al 2001, Dube et al 2005, bulls (Cormier & Bailey 2003) and buffalo (Roy & Atreja 2008). Moreover, other studies have revealed that certain tyrosine phosphoproteins become localized to the sperm surface overlying the acrosome during capacitation suggesting a key role of these proteins in sperm-zona binding (Asquith et al 2004, Piehler et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a capacitation-associated redistribution of phosphotyrosine residues to the acrosome has been reported in boars (Petrunkina et al 2001, Tardif et al 2001, bulls (Cormier & Bailey 2003) and buffalo (Roy & Atreja 2008), and specific phosphotyrosine proteins localized over the acrosomal region have been postulated to be involved in the zona pellucida interaction and/or fusion events (Leyton & Saling 1989, Naz et al 1991, Ficarro et al 2003, Dube et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Only sperm samples with over 95% of the sperm showing progressive motility were used for the experiments. Sperm capacitation was induced according to the method reported by of Tardif et al (2001), with slight modifications. The washed sperm were incubated either in 15 ml of Non-cap medium or in Cap medium (5!10 6 cells/ml) at 37 8C for 3 h in a 5% CO 2 atmosphere.…”
Section: Preparation Of Cauda Epididymal Sperm and Induction Of Capacmentioning
confidence: 99%
“…The noncapacitating medium (NCM) contained 2.7 mM KCl, 1.5 mM KH 2 PO 4 , 8.1 mM Na 2 HPO 4 , 137 mM NaCl, 5.55 mM glucose, and 2 mM pyruvate (pH 7.4). Both media have been described previously (Tardif, 2001). …”
Section: Mediamentioning
confidence: 99%